2007
DOI: 10.1103/physreve.76.021303
|View full text |Cite
|
Sign up to set email alerts
|

Spatial force correlations in granular shear flow. II. Theoretical implications

Abstract: Numerical simulations are used to test the kinetic theory constitutive relations of inertial granular shear flow. These predictions are shown to be accurate in the dilute regime, where only binary collisions are relevant, but underestimate the measured value in the dense regime, where force networks of size ξ are present. The discrepancy in the dense regime is due to non-collisional forces that we measure directly in our simulations and arise from elastic deformations of the force networks. We model the non-co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 46 publications
4
23
1
Order By: Relevance
“…We further expect it to depend on details such as particle size distribution [25] as the maximum packing fraction changes. The size of the clusters we describe is likely related to an interparticle force correlation length ξ whose growth was shown by Lois et al [28] to correspond with a transition from sparse to dense flow. They demonstrated that the transitional value of ξ depends on the interparticle restitution coefficient, which we expect will influence our segregation transition as well.…”
Section: (C) and (D)supporting
confidence: 52%
“…We further expect it to depend on details such as particle size distribution [25] as the maximum packing fraction changes. The size of the clusters we describe is likely related to an interparticle force correlation length ξ whose growth was shown by Lois et al [28] to correspond with a transition from sparse to dense flow. They demonstrated that the transitional value of ξ depends on the interparticle restitution coefficient, which we expect will influence our segregation transition as well.…”
Section: (C) and (D)supporting
confidence: 52%
“…The result that g(r) behaves the same along both diagonals is different from the earlier finding of an angular dependence of the correlation length in shearing systems [7] with minimum and maximum along the different diagonals. The reason for this difference is not clear, but we speculate that it is related to the very different dynamics in their system, which is also reflected in the oscillatory behavior of their velocity correlation function.…”
Section: Spatial Dependencecontrasting
confidence: 56%
“…A large correlation length was however found in Ref. [7] and they also argued for a pronounced angular dependence of the velocity correlations [8].…”
Section: Introductionmentioning
confidence: 96%
“…Mean force on the obstacle [52][53][54][55][56]). This issue is not discussed in detail in this paper.…”
Section: Control Flows Without An Obstaclementioning
confidence: 99%